2013
DOI: 10.1155/2013/713791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subgrains on the Performance of Mono-Like Crystalline Silicon Solar Cells

Abstract: The application of Czochralski (Cz) monocrystalline silicon material in solar cells is limited by its high cost and serious light-induced degradation. The use of cast multicrystalline silicon is also hindered by its high dislocation densities and high surface reflectance after texturing. Mono-like crystalline silicon is a promising material because it has the advantages of both mono- and multicrystalline silicon. However, when mono-like wafers are made into cells, the efficiencies of a batch of wafers often fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…[36] Sub-GBs, though with a small deviation of crystalline lattice orientation, usually cause distorted regions [13,21] which could attract impurity precipitating and result in dislocation generation, significantly decreasing the minority carrier lifetime because of their strong recombination activity. [37][38][39] Lantreibecq et al [40] observed sub-GBs with TEM and SEM. They found that sub-GBs were constituted by a set of dense, perfectly organized immobile dislocations aligned along the growing direction and having an edge character.…”
Section: Subgrain Boundariesmentioning
confidence: 99%
“…[36] Sub-GBs, though with a small deviation of crystalline lattice orientation, usually cause distorted regions [13,21] which could attract impurity precipitating and result in dislocation generation, significantly decreasing the minority carrier lifetime because of their strong recombination activity. [37][38][39] Lantreibecq et al [40] observed sub-GBs with TEM and SEM. They found that sub-GBs were constituted by a set of dense, perfectly organized immobile dislocations aligned along the growing direction and having an edge character.…”
Section: Subgrain Boundariesmentioning
confidence: 99%
“…Other differences include taking the effects of wind speeds on solar module cooling into account, as well as the light-induced degradation (LID) phenomenon. LID is the additional long-term degradation of solar cell performance when exposed to light, especially pronounced in monocrystalline solar cells [29]. Because it varies wildly with the quality of the solar cell silicon, we choose not to model this behaviour in the presented model.…”
Section: Pv System Model Evaluationmentioning
confidence: 99%
“…Subgrains are observed in all silicon ingots that are produced by casting processes for PV applications: in cast mono (cm-Si) [4][5][6], high-performance multicrystalline (HPmc-Si), [7] and conventional multicrystalline (mc-Si) silicon [8]. For mc-Si, either grains with <110> or <111> growth directions were reported to have the highest dislocation density [8][9][10].…”
Section: Introductionmentioning
confidence: 99%